(untitled) (Federal University Gusau Faculty of Education Journal, 2026)
The research examined the Evaluation of Availability and Adequacy of Instructional Materials for Teaching and Learning of Economics in Senior Secondary Schools in North West, Nigeria. The objective of this study is to find out the availability and adequacy of instructional materials for teaching and learning of Economics in senior secondary schools in North West, Nigeria. The study established two research questions and two null hypotheses which were subsequently tested for the study. The study reviewed two related theories, concepts and thirty (30) relevant empirical studies. The study employed a descriptive survey research design. The target population of the study comprised of one hundred and eight thousand, nine hundred and seventy-four (108,974) respondents which included Senior Secondary School Two (SS II) Economics students and Economics teachers from the seven states of the North West Geo-Political Zone of Nigeria. A sample size of three hundred and eighty-four (384) respondents were selected for the study using multistage sampling techniques. A 4-point-likert scale questionnaire with fifty (50) items were used as instruments for this study. The instrument was pilot tested and the reliability coefficients of 0.85 was obtained using Cronbach’s Alpha. The data collected was analyzed using descriptive and inferential statistic. Frequency and mean was used to analyze the research questions while the two null hypotheses were tested using Mann-Whitney U-test at 0.05 level of significance. This is because, the data obtained was ordinal and discreet in nature. The results indicated the retaining of all the hypotheses at a significance level of 0.05. in conclusion, the study’s findings revealed that, instructional materials for teaching and learning of Economics in Senior Secondary Schools in North West, Nigeria were available. The finding also disclosed that, some of the instructional materials were inadequate for teaching and learning of Economics in Senior Secondary Schools in North West, Nigeria. The study concluded that, instructional materials for teaching and learning of Economics in Senior Secondary Schools in North West, Nigeria were generally available. However, a critical gap was observed in terms of adequacy in the materials provided to the schools. Therefore, it could also be concluded that, availability of instructional materials alone would not bring about effective and efficient teaching and learning processes in Economics unless such materials are fully adequate in schools. Based on the findings and conclusion of this study, the following recommendations were made: Governments, school administrators, teachers and other stakeholders should maintain and sustain the steady supply of instructional materials for teaching and learning of Economics in Senior Secondary Schools in North West, Nigeria. Furthermore, Governments, policymakers, school management and stakeholders should also provide adequate instructional materials for teaching and learning of Economics in Senior Secondary Schools in North West, Nigeria.